PEMBELAJARAN MENGANALISIS MENULIS PUISI DENGAN MENGGUNAKAN PENDEKATAN KONTEKSTUAL IMAJINATIF - Rendi Handiwiguna; Fitria Hasanatul Mila; Dida Firmansyah (IKIP Siliwangi, 2018)
The reason researchers in choosing the title is the examine the ability of students in “Writing Poetry”. This study aims to introduce the learning of writing materials spontaneously. From the results of this activity, students can develop creativity and imagination that later developed become a poem, cultivate a critical attitude to the problems that occur in everyday life, and foster the attitude of daring to issue ideas or ideas about an accurate problem. This study uses an imaginative contextual approach where the teacher presents the situation real world into the classroom and encourage students to make connections between their knowledge as a process of rebuilding perceptions of understanding. This research data obtained through observation, interview, and test. Then the data is analyzed students’ creativity divided into two cycles. Between cycle 1 and cycle 2 gradually increased by an average of 52,10% increased to 74,40%.